2001
DOI: 10.4049/jimmunol.166.1.544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Roles of ICAM-1 in Neutrophil Transmigration Using a Reconstituted Mammalian Cell Expression Model: Implication of ICAM-1 Cytoplasmic Domain and Rho-Dependent Signaling Pathway

Abstract: Interaction between ICAM-1 (CD54) and fibrinogen (fg) has been shown to enhance leukocyte adhesion, but its specific role in the process of migration across endothelial cell junctions remains unclear. To overcome the problem of multiple adhesion receptors found on endothelial cells, we have engineered stable Chinese hamster ovary cell lines expressing ICAM-1 (Chinese hamster ovary ICAM-1). The transfection of ICAM-1 alone in these cells is sufficient to recapitulate the entire process of neutrophil adhesion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 37 publications
6
86
0
3
Order By: Relevance
“…We also generated COS-7 cells that express the ICAM-1 lacking intracellular domain (C-terminal 28 amino acids; IC1⌬CTD_GFP) in order to investigate potential function of intracellular domain on the distribution and localization of ICAM-1. Although earlier studies have utilized the CHO cell system to overcome the problem of multiple adhesion receptors found on endothelial cells (Sans et al, 2001;Carman et al, 2003), others have found that Chinese hamster ovary (CHO) cells express endogenous cell surface molecules that mediate T-cell costimulation (Gaglia et al, 2001). We also noticed that this uncharacterized molecule could mediate T-cell adhesion potentially through its interaction with LFA-1 (data not shown).…”
Section: The Distribution and Dynamic Movements Of Icam-1 On Transfecmentioning
confidence: 71%
See 3 more Smart Citations
“…We also generated COS-7 cells that express the ICAM-1 lacking intracellular domain (C-terminal 28 amino acids; IC1⌬CTD_GFP) in order to investigate potential function of intracellular domain on the distribution and localization of ICAM-1. Although earlier studies have utilized the CHO cell system to overcome the problem of multiple adhesion receptors found on endothelial cells (Sans et al, 2001;Carman et al, 2003), others have found that Chinese hamster ovary (CHO) cells express endogenous cell surface molecules that mediate T-cell costimulation (Gaglia et al, 2001). We also noticed that this uncharacterized molecule could mediate T-cell adhesion potentially through its interaction with LFA-1 (data not shown).…”
Section: The Distribution and Dynamic Movements Of Icam-1 On Transfecmentioning
confidence: 71%
“…To this end, peptides comprising the 14 C-terminal amino acids or RKIKK residues were used to antagonize the binding potential of ICAM-1-binding/signal partners. Such ICAM-1 peptides were fused to the penetratin sequence to facilitate the uptake of peptides into cells (Hall et al, 1996;Sans et al, 2001). We assessed the effects of penetratin-ICAM-1 peptides (P-CTD, RQRKIKKYRLQQAQ; P-RKIKK, and RKIKK) for the leukocyte adhesion to and transmigration through HUVECs under the static flow condition.…”
Section: Cell-permeant Peptides Comprising the Rkikk Motif Attenuate mentioning
confidence: 99%
See 2 more Smart Citations
“…al., 2001;Sans et. al., 2001), phagocytosis (Rubel et al, 2001(Rubel et al, , 2002, cytokine and chemokine expression (Fan and Edgington, 1993;RL Perez 1995;Smiley et.…”
Section: Discussionmentioning
confidence: 99%